Efficiency of Introduction of a Cost Controlling System at the Enterprise - SHEVCHENKO, Svetlana Y.; LENKOVA, Olga V. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The research indicates the relevance of controlling the costs of main gas transportation from the point of the modern concept of sustainable development. A review of the current state of the industry and enterprises at the macro-, meso- and microeconomic level is provided. The author's scheme of assessing the impact of the cost controlling system on business results is presented. The possible impact of the implementation of cost controlling on the quantitative and qualitative indicators of the company is considered. The relationship between different types of efficiency with the resource concept of the organization's efficiency is shown. The cumulative result of testing the methodological tools of the cost controlling system at the gas transportation enterprise is provided. At the same time, the testing calculation is based on the implementation of the combination of the controlling tools: ABC methodology, benchmarking, and building a value chain. The results of the calculation of the expected effect of the implementation of cost controlling in terms of the concept of sustainability (meso-level of evaluation) are provided.